Media Baru Dan Budaya Populer Di Aceh: Kajian Nilai-Nilai Dakwah Transformatif Dalam Aceh Pop Culture Fest Fest Di Kota Banda Aceh - Syukri Syamaun; Syukur Kholil (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research is a mini-qualitative research that aims to synthesize the transformative dawah values that exist in the Aceh Pop Culture Fest which is being held in Banda Aceh at 18 to 20 March 2023, the Aceh Culture and Tourism Office. Research data were obtained from 2 sources, namely: the Aceh Culture and Tourism Office website which contains activity information about the Aceh Pop Culture Fest Fest and video recordings of the festival during the activity. The results of the study show that the Aceh Pop Culture Fest Fest is a cultural accompaniment carried out among the younger generation. This activity contains transformative dawah values because it is oriented towards empowering people from bad to good conditions, from weak to strong conditions, so they can be competent in a global world.